Production and Consumption of Research in Police Agencies in the United States, 1989-1990 - Klockars, Carl B. ([Verlag nicht ermittelbar], 1997)
The purpose of this study was to describe the dynamics of police research, how the role and practice of research differ among police agencies, and why this appears to happen. This study also attempts to answer, on a national scale, four fundamental questions: (1) What is police research? (2) Who does it? (3) Why is it done? and (4) What impact does it have? In addition to describing the overall contours of the conduct of research in United States police agencies, this study also sought to explore the organizational dynamics that might contribute to understanding the different roles research plays in various types of police organizations. Questionnaires were mailed in 1990 to 777 sheriff, municipal, county, and state police agencies selected for this study, resulting in 491 surveys for analysis. Respondents were asked to identify the extent to which they were involved in each of 26 distinct topic areas within the past year, to specify the five activities that consumed most of their time during the previous year, and to describe briefly any projects currently being undertaken that might be of interest to other police agencies. A second approach sought to describe police research not in terms of the topics studied but in terms of the methods police used to study those topics. A third section of the questionnaire called for respondents to react to a series of statements characterizing the nature of research as practiced in their agencies. A section asking respondents to describe the characteristics of those responsible for research in their agency followed, covering topics such as to whom the research staff reported. Respondent agencies were also asked to evaluate the degree to which various factors played a role in initiating research in their agencies. Finally, questions about the impact of research on the police agency were posed.